On Proposal To Regulate Abuse Of Superior Bargaining Position: Lessons From Other Jurisdictions - Suyawan, Meirani; Tanjung, Kurnia Togar Pandapotan (UI Scholars Hub, 2020)
The latest version of the draft bill regarding Law on the Prohibition of Monopolistic Practices and Unfair Business Competition has added new arrangements about the abuse of a superior bargaining position. The new law proposal which is intended to amend existing Indonesian competition law (Law Number 5 Year 1999) stipulates that any business actor is prohibited from abuse its superior bargaining position within a partnership agreement with other less dominant entities. Under Law Number 20 Year 2008 on Micro, Small and Medium Enterprises, a partnership agreement means any agreement made between micro, small and medium enterprises and large enterprises like state or privately owned national businesses, joint ventures and foreign businesses that conduct economic activities in Indonesia. Such a condition makes many antitrust experts or economists question the relevancy of regulating abuse of superior bargaining position under competition law. However, several jurisdictions –Japan, Korea, Taiwan, France, and Germany- have regulated the abuse of superior bargaining position under their national competition laws.